The impact of Medicaid on medical utilization in a vulnerable population: Evidence from COFA migrants. (27th July 2020) - Halliday, Timothy J.; Akee, Randall Q.
Abstract: In March 2015, the State of Hawaii stopped covering the majority of migrants from countries belonging to the Compact of Free Association (COFA) in its Medicaid program. COFA migrants were required to obtain private insurance in the exchanges established under the Affordable Care Act. Using statewide hospital discharge data, we show that Medicaid‐funded hospitalizations and emergency room visits declined in this population by 31% and 19%, respectively. Utilization funded by private insurance did increase but not enough to offset the declines in Medicaid‐funded utilization. We show that the expiration of benefits increased uninsured ER visits. Finally, we exploit a feature of the policy change to provide evidence that the declines in utilization are due to higher rates of uninsured migrants rather than higher levels of cost sharing on private plans.